Impedance and dielectric properties of Nb-doped Pb(Zr0.52Ti 0 48)O3 ceramics - P. Ketsuwan (2018)
The compositions of Pb(Zr0.52Ti0 48)O3 doped with 1-6 mole% Nb content were prepared by a conventional mixed oxide technique. It was found that the phase formed depended on the dopant concentration. At lower concentration, the dominate phase was the tetragonal. With increasing Nb content the rhombohedral phase tended to increase. Furthermore, the Curie temperature (Tc) and dielectric constant decreased with increasing Nb concentration and the dielectric maximum peaks were broadened with more rhombohedral phase presence, causing the diffused ferroelectric-paraelectric phase transition. The impedance of the samples decreased with increasing temperature and it was also observed that the impedance increased with increasing Nb concentration. © 2008 Trans Tech Publications, Switzerland.